Keputusan Pembelian Air Mineral Dalam Kemasan Di Kabupaten Jepara - Damayanti, Melisa; Musyafa', Musyafa' (Jurnal Iqtisaduna, 2024)
The purpose of this study was to examine how product knowledge, price, religiosity, and halal labeling influence consumers' decision to purchase bottled mineral water in 16 sub-districts located in Jepara Regency, Indonesia. Quantitative research methodology was applied to a population of individuals who have used bottled mineral water. The research sample amounted to 100 respondents obtained from the Lemeshow formula. Data were collected through questionnaires and used analytical techniques of validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The findings of the analysis show that although product knowledge, price, and halal label significantly influence consumers' decision to buy bottled mineral water, religiosity has no significant impact on the decision, indicating that consumers prioritize functional and practical factors over aspects of religiosity, among these variables, the halal label has the greatest influence on purchasing decisions. The results of this study provide valuable information for manufacturers and marketers to create more successful marketing strategies by considering the elements that influence consumer preferences.